Do cool sh*t : quit your day job, start your own business, and live happily ever after - Agrawal, Miki (HarperBusiness, an imprint of HarperCollinsPublishers, 2013)
"An inspiring, irreverent manifesto for those seeking to blaze their own path to entrepreneurship and find fulfillment and happiness through bold action and big ideas. Have you ever wondered if it's possible to make a career out of something you love? Or how to march through life with a purpose and get the most out of every second? Miki Agrawal, entrepreneur, angel investor, and cool-sh*t-doer, has figured it out. Here Miki shares her own adventures in entrepreneurship and life, from learning to step out of her comfort zone in a foreign country to achieving her dream of playing soccer for the New York Magic to partnering with Tony Hsieh of Zappos.com to launch her dream business. In Do Cool Sh*t, Miki shows you how to start your own business, fund it on a shoestring budget, convene the perfect group to brainstorm your business plan, test your product, get great (free) press coverage, and more--all while living a life you're proud of."-- From dust jacket flap.